Neuronavigation with the Universal Probe to Access Intracranial Targets - Waran, V.; Chandran, H.; Devaraj, P.; Ravindran, K.; Rathinam, A. K.; Balakrishnan, Y. K.; Tung, T. S. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Introduction The universal probe is a tool devised to allow navigation-directed biopsies and drainage procedures to be performed in a simple manner using a single hardware and software.Aim To assess the efficacy and safety of the universal probe.Results We used the universal probe in a total of 17 patients for 10 biopsies and 8 drainage procedures. We were able to achieve our set objectives in all 18 procedures. We did not encounter any complications using this device.Conclusion The universal probe enabled a variety of navigation-based procedures to be carried out using only a single software and hardware.
Keywords: navigation; biopsy; drainage; probe